Physiological responses in relation to performance during competition in elite synchronized swimmers - Rodriguez-Zamora, L.; Iglesias, X.; Barrero, A.; Chaverri, D.; Erola, P.; Rodriguez, F. A. (PLOS ONE, 2012)
We aimed to characterize the cardiovascular, lactate and perceived exertion responses in relation to performance during competition in junior and senior elite synchronized swimmers. Methods